ANALISIS BUTIR SOAL UJIAN AKHIR SEMESTER DALAM PENERAPAN KURIKULUM 2013 DI KELAS III SD NEGERI 111 PEKANBARU - Ririn Amalia; Otang Kurniaman; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aimed to describe the quality of the items qualitatively on a multiple choice test and quality items quantitatively on a multiple choice test in the form of validity, reliability, level of difficulty as well as distinguishing features about the final exams in the implementation of the curriculum in 2013 in class III Elementary School 111 State Pekanbaru academic year 2015/2016. This research is descriptive qualitative and quantitative. Data collection methods used in the study is the document. Subjects in this study is the third grade students of State Elementary School 111 Pekanbaru and all items Final Exam Odd Semester III Class 111 Pekanbaru Public Elementary School Academic Year 2015/2016. Research shows that in terms of material, construction and language exam end of semester of grade III 111 Pekanbaru Public Elementary School has been very good. Based on the validity of an item indicates that a valid items amounted to 89 grains (74.17%) and invalid items amounted to 31 grains (25.83%). Based on the reliability including the matter that has high reliability that is equal to 0.80. Based on the Power differentiator in mind that items with very bad differentiator totaling 17 items (14.1%), poor amounted to 14 grains (11.7%), good enough grain amounted to 18 (15%), either 31 grains (25.8%) and excellent amounted to 40 eggs (33.3%). Based on the level of difficulty is known that the items are very difficult 1 point (0.83%), difficult 2 grains (1.67%), while 41 items (34.1%), is 28 grains (23.3%), and very easy 48 point (40%).Key Words: Analysis, Grain Problem, Curriculum 2013